Analisis Kinerja Inverter VSD terhadap Kecepatan Gerakan pada Mesin Pencetak Kerupuk - Muhammad Akhlis Rizza; Wenda Prasta Wahyuadi (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
Mr. Ujang Cracker Factory, located in Pakiskembar Village, Pakis District, Malang Regency, is one of the UMKM that produces crackers. Most of the machines used in cracker processing at Mr. Ujang Cracker Factory still use a simple mechanical system. One of these machines is a cracker molding machine, where the speed is still adjusted manually by replacing the pulley. This study aims to recondition the cracker molding machine by adding a control panel in the form of a VSD inverter with the aim of facilitating the speed control process in operating the cracker molding machine. This study was conducted by analyzing the consistency of the influence of frequency and pulley diameter variations on the speed of the electric motor and mechanical movements in the cracker molding machine. The results of the study show that the frequency of the VSD inverter and the pulley diameter have a significant effect on the entire mechanism of the cracker printing machine. Based on the standard deviation value, the consistency of the pressing movement speed was obtained at a frequency of 40 Hz with a pulley diameter of 2 inches. From this study, it can be concluded that the overall frequency of the VSD inverter is the main parameter in determining the speed and stability of the cracker printing machine. Meanwhile, the variation in pulley diameter only serves as an additional mechanical adjustment to increase or decrease the output speed from the electric motor to the mechanical movement of the cracker printing machine.